Paraguay’s approach to biotechnology governance: a comprehensive guide - Benítez Candia, Nidia; Ulke Mayans, María Gabriela; Sotelo, Pablo Hernán; Nara Pereira, Eva; Arrúa Alvarenga, Andrea Alejandra; Fernández Ríos, Danilo (Frontiers in Bioengineering and Biotechnology, 2024)
This study analyzes Paraguay's biotechnology regulatory framework and its alignment with international standards amid biotechnological advancements. It also identifies areas of improvement for enhancing framework effectiveness. Through this work, we aim to provide a resource for policymakers, stakeholders, and researchers navigating Paraguay's biotechnology regulation.